FIRST CASE REPORT OF POPPERS MACULOPATHY WITH CANNABIS (CHARAS) IN PAKISTAN - Shahid, Erum; Saleem, Afsheen; Fasih, Uzma (Journal of Ayub Medical College Abbottabad, 2022)
Poppers is a recreational drug common in gay communities often used for euphoria and myorelaxation. It causes yellow foveal discoloration with disruption of outer segments of the foveal photoreceptors called Popper's maculopathy. We present first case of poppers maculopathy with use of Charas (Cannabis) from Pakistan. A 32-year-old transgender presented with bilateral gradual decrease in vision over the last two years. He gave past history of smoking cigarette and Cannabis (Charas). His visual acuity was 6/60 unaided and 6/36 with the help of pin hole bilaterally. Near vision was N/18 and Color vision was 12/12 on Ishihara test plate bilateral. Fundus examination revealed a yellow foveal spot at the posterior pole bilaterally. Optical coherence tomography (OCT) showed disruption of inner outer segment of foveal cones. Patient was followed up at three months after prescribing oral leutins with no improvement in vision.